2003
DOI: 10.1080/14017430310014948
|View full text |Cite
|
Sign up to set email alerts
|

Unspecific elevation of plasma troponin‐T and CK‐MB after coronary surgery

Abstract: Substantial early elevations of plasma CK-MB and troponin-T occurred in patients with no or minimal permanent myocardial injury after CABG. Unspecific release was most pronounced during the timeframe that is usually studied to evaluate myocardial protective strategies or to compare revascularization procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…The troponins have later peak values than traditional biomarkers, with increased plasma levels for several days (7). However, troponins are not spared from unspecific release early after surgery and are more expensive to analyze (8). Thus the troponins are suitable as a late marker, preferably analysed on the third or fourth postoperative day, when interfering diagnostic noise can be avoided (1,11,12).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The troponins have later peak values than traditional biomarkers, with increased plasma levels for several days (7). However, troponins are not spared from unspecific release early after surgery and are more expensive to analyze (8). Thus the troponins are suitable as a late marker, preferably analysed on the third or fourth postoperative day, when interfering diagnostic noise can be avoided (1,11,12).…”
Section: Discussionmentioning
confidence: 94%
“…Traditional markers for myocardial injury, such as ASAT and CKMB, have been used after surgery but have low specificity due to early unspecific release, i.e. diagnostic noise (8). More recently studies have been published which suggest that troponins may improve sensibility and specificity in the diagnosis of permanent myocardial injury (2,4Á7,10).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 1 shows that even though we did not find an over all difference in cTnT between the two groups, in our study a cTnT value obtained early (4 h) after termination of CPB was numerically higher in the autotransfusion group compared with the control group. Dahlin et al (4) have shown that substantial early and unspecific elevation of cTnT occurs after CABG in patients with no or minimal myocardial damage. In conjunction with this it has been suggested that the diagnosis of a peri‐operative myocardial infarction should be based on the presence of a sustained high level of cTnT 48 h or more after CABG (4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…In the ‘non‐surgical’ setting, biochemical markers of myocardial damage such as myocardial band (MB) isoenzymes of creatine kinase (CK‐MB), cardiac troponin I (cTnI), and cardiac troponin T (cTnT) are used to detect myocardial infarction, and the diagnostic performance of these markers of myocardial injury is well described (1–3). However, after cardiac surgery the diagnosis of peri‐operative myocardial infarction is interfered by an unspecific elevation of CK‐MB, cTnI and cTnT that is unrelated to permanent myocardial injury (4), and the diagnostic discrimination limits of these biochemical markers after cardiac surgery remain unresolved (5–7).…”
mentioning
confidence: 99%